DIAGNOSIS AND MANAGEMENT OF LYMPHOMA IN A GERMAN SHEPERD DOG : A CASE REPORT - G.R. Baranidharan; Rajat Sagare; C. Jayanthy; A. Gopalakrishnan; S. Abinaya; Ashi Krishna (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A case was diagnosed as canine multicentric lymphoma based on clinical presentation, FNAC and ultrasonography and was treated with CHOP-19 protocol and remission was observed on 9th week but the protocol was continued up to 19th week and no signs of relapse was noticed. The animal was monitored every month for month after the treatment (19 weeks) animal showed no signs of reoccurrence up to 7 months. Multicentric lymphoma is a disease that the general practitioner can manage; it does not require referral to a specialized practice.